Pengetahuan Remaja Putri tentang Terapi Musik Klasik sebagai Pengurangan Nyeri Menstruasi - Nurbaiti, Nurbaiti; Febrina, Ria (Prosiding Seminar Kesehatan Nasional, 2023)
For young women, the incidence of dysmenorrhea is very disturbing in learning, even not following learning, it is difficult to concentrate because of the discomfort felt while menstruating, emotional conflicts, tension, anxiety. Dysmenorrhea that is not treated immediately can result in disturbances in daily activities or activities. day. One of the non-pharmacological treatments is the breathing relaxation method in combination with music. Music is an effective distraction technique where music can reduce physiological pain, stress and anxiety by diverting one's attention from pain. This study aims to determine the knowledge of young women about classical music therapy as a reduction in menstrual pain, this study uses a descriptive, this study was conducted at Baiturrahim Jambi Vocational School, the population in this study were all young women in Baiturrahim Vocational School totaling 139 students, samples taken in This study uses a total sampling technique. This research was conducted on January 12, 2022 at Baiturrahim SMK Jambi. The results achieved in this study, most of the respondents aged 15 years were 55 respondents (39.56%), 16 years old were 45 respondents (32.37%), 14 years old were 39 respondents (28.05%). While the knowledge of young women obtained by most of the respondents with sufficient knowledge of 88 (63.3%) and good knowledge of 51 (36.7%). The conclusion in this study is that the majority of adolescent girls are 15 years old and the knowledge of young girls is included in the sufficient category about the benefits of music therapy for reducing pain during menstruation (diesmenorrhea). It is recommended that young women can take part in activities that can provide knowledge, especially about health and it is hoped that the research team can carry out educational activities on a regular basis to provide knowledge to the community.Â